A síndrome maníaco depressiva na Epidemia HIV/AIDS: vacinas ineficazes versus combinações de drogas eficazes - Sá, Carlos Alberto Morais de (Brazilian Journal of Sexually Transmitted Diseases, 1997)
Aftermore than a decade of research wirhout effective and safe HIV vaccines there is a general agreement that more fundamental research on vaccine development is required. On the contrary, anti-HIV combination therapy may eradicate HIV in primary infection and avoid vertical cransmission. ln more advanced stages of HIV infection, double or tripie combination therapy may suppress HIV replication and confer clinical benefit. Effective control of HIV replication may be possible in some parients. The cost, toxicity, and compliance issues may forestall more aggressive combinations